The Black Cultural Front : Black Writers and Artists of the Depression Generation - Dolinar, Brian (Book collections on Project MUSE., 2012)
The Black Cultural Front describes how the social and political movements that grew out of the Depression facilitated the left turn of several African American artists and writers. The Communist-led John Reed Clubs brought together black and white writers in writing collectives. The Congress of Industrial Organizations's effort to recruit black workers inspired growing interest in the labor movement. One of the most concerted efforts was made by the National Negro Congress (NNC), a coalition of civil rights and labor organizations, which held cultural panels at its national conferences, fought.